2015
DOI: 10.1113/jphysiol.2014.281014
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic P2X3‐containing receptors in gustatory nerve fibres mediate responses to all taste qualities in mice

Abstract: Key pointsr Acute inhibition of purinergic receptors with a selective P2X3 antagonist prevents transmission of information from taste buds to sensory nerves.r The P2X3 antagonist has no effect on taste-evoked release of ATP, confirming the effect is postsynaptic.r The results confirm previous results with P2X2/3 double knockout mice that ATP is required for transmission of all taste qualities, including sour and salty. Previously, ATP was confirmed to be required for bitter, sweet and umami tastes, but was que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 47 publications
3
71
0
Order By: Relevance
“…Among the taste cell types, only Type III cells form conventional synapses on sensory nerve fibers (Yang et al, 2000(Yang et al, , 2004; they release GABA and serotonin, which are likely to be neuromodulators rather than neurotransmitters (Chaudhari, 2014). By contrast, ATP released by Type II cells functions as a bona fide neurotransmitter, as it is required for the transmission of all taste information from taste buds to sensory nerves (Finger et al, 2005;Vandenbeuch et al, 2015). The source of the ATP required for Type III cell signaling to afferent fibers is not known.…”
Section: An Overview Of the Taste Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the taste cell types, only Type III cells form conventional synapses on sensory nerve fibers (Yang et al, 2000(Yang et al, , 2004; they release GABA and serotonin, which are likely to be neuromodulators rather than neurotransmitters (Chaudhari, 2014). By contrast, ATP released by Type II cells functions as a bona fide neurotransmitter, as it is required for the transmission of all taste information from taste buds to sensory nerves (Finger et al, 2005;Vandenbeuch et al, 2015). The source of the ATP required for Type III cell signaling to afferent fibers is not known.…”
Section: An Overview Of the Taste Systemmentioning
confidence: 99%
“…Type I cells express membrane-localized NTPDase2 (Entpd2), an ectoATPase that converts ATP to ADP. Type II cells use ATP as a neurotransmitter to signal to sensory nerves (Finger et al, 2005;Vandenbeuch et al, 2015), yet Type II cells lack presynaptic specializations; rather, Type II cells release ATP in a non-vesicular manner (Huang et al, 2007;Romanov et al, 2013Romanov et al, , 2007, probably via CALMH1 ion channels (Taruno et al, 2013). Thus, NTPDase2-expressing Type I cells are likely to clear excess ATP released by Type II cells to ensure efficient neurotransmission (Bartel et al, 2006;Finger et al, 2005;Vandenbeuch et al, 2013).…”
Section: An Overview Of the Taste Systemmentioning
confidence: 99%
“…[56]. ATP release by taste buds is the first step in all modalities of taste sensation: the ATP activates P2X2/P2X3-subunit-containing receptors on the gustatory nerve [57]. An analogous signalling role from urothelium to primary afferent nerves has been inferred for sensing bladder distension [58].…”
Section: Following Cdna Cloningmentioning
confidence: 99%
“…One confounding factor with such trials of P2X3 receptor antagonists will be the difficulty in conducting 'blind' trials. ATP is a transmitter released by taste buds and it activates P2X3-subunit-containing receptors on gustatory nerves [57], and all the patients in the trial who took AF-219 reported disturbance of taste [99].…”
Section: Therapeutic Exploitationmentioning
confidence: 99%
“…Upon stimulation, taste bud cells, which are dedicated to specific taste qualities, release transmitters (Chaudhari and Roper, 2010;Roper, 2013), including ATP (Finger et al, 2005;Taruno et al, 2013) that bind to their corresponding receptors (Huang et al, 2011b;Kinnamon and Finger, 2013) and transmit information to sensory afferent fibers (Barretto et al, 2015;Vandenbeuch et al, 2015). Taste bud cells communicate with each other [i.e.…”
Section: Introductionmentioning
confidence: 99%